1984
DOI: 10.2355/isijinternational1966.24.532
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution rate of burnt dolomite in molten FetO-CaO-SiO2 slags.

Abstract: SynopsisCylinders of burnt dolomite with the apparent porosities of 20 to 35 were immersed into molten FetO-CaO--Si02 slaps at temperatures of 1 950 to 1 425 °C and rotated at 100 to 400 rpm. The dissolution rates were determined by measuring the decrease in radius of cylinder.The dissolution rate increased with increases in temperature and revolutional speed of cylinder, but was not affected by the difference in apparent porosity of burnt dolomite. From the analysis of experimental results, it was concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 1 publication
11
61
0
1
Order By: Relevance
“…The results obtained are consistent with the conclusions made by Umakoshi. et al 15) about limitation of lime dissolution process by magnesium oxide in slag systems with FeO content above 20%.…”
Section: The Calculation Of the Diffusion Coefficients Of Lime Dissolmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained are consistent with the conclusions made by Umakoshi. et al 15) about limitation of lime dissolution process by magnesium oxide in slag systems with FeO content above 20%.…”
Section: The Calculation Of the Diffusion Coefficients Of Lime Dissolmentioning
confidence: 99%
“…The increase in the concentration of MgO in lime slows down the dissolution rate of the samples. In the work 4,15) authors measured the rate of calcined dolomite samples СаСО 3 ·MgCO 3 dissolution in the slag with the composition FexO-CaO-SiO 2 , containing FeO from 20 to 65%. Authors suggested a limitation of the MgO diffusion in the slag containing FeO more than 20% through the surface layer at the interface.…”
Section: Determination Of Lime Mass Transfer Coefficients In the Modementioning
confidence: 99%
See 1 more Smart Citation
“…A so-called J-factor was introduced to express mass transfer in the liquid. Umakoshi et al [7] also used this method to investigate the dissolution rate of burnt dolomite in converter slag. They reported that the dissolution rate was not affected by the porosity of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…THE rotating disk/cylinder (rod) method has been widely applied to study the dissolution of solids in liquids for decades, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in particular for high-temperature systems such as dissolution of solid metals into liquid metals, and dissolution of ceramic solids into liquid oxides (slags). While valuable information have been gained by these studies, some misconceptions in using this method need to be addressed and analyzed.…”
Section: Introductionmentioning
confidence: 99%